"Portret wisielca". Retoryczne funkcje kryminałów retro Marcina Wrońskiego = "Portret Wisielca" ("he Portrait of a Hanged Man". Rhetorical functions of retro crime novels by Marcin Wroński - Ryszkiewicz, Mirosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"The retro crime novel" is one of the categories in the area of crime fiction that has been frequently described, mainly by literary criticism. Thus, not to repeat the already known assumptions, the article pays attention predominantly to one problem, specifically addressed in retro crime novels, namely: attracting the reader, both the model one and the empirical one, which is defined by classical rhetoric as "captatio benevolentiae".
Keywords: powieść kryminalna retro; literaturoznawstwo